2010
DOI: 10.1093/alcalc/agq017
|View full text |Cite
|
Sign up to set email alerts
|

Why is Disulfiram Superior to Acamprosate in the Routine Clinical Setting? A Retrospective Long-Term Study in 353 Alcohol-Dependent Patients

Abstract: This study supports the thesis that supervised DSF is an important component of alcoholism treatment, and it appears to be more effective than the treatment with ACP particularly in patients with a long duration of alcohol dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 33 publications
(28 reference statements)
4
21
0
3
Order By: Relevance
“…8 This result is in line with previously published data. 4 One could argue that our subjects may represent a less severe phenotype of alcohol addiction.…”
Section: Discussionsupporting
confidence: 93%
“…8 This result is in line with previously published data. 4 One could argue that our subjects may represent a less severe phenotype of alcohol addiction.…”
Section: Discussionsupporting
confidence: 93%
“…The superiority of disulfiram over acamprosate and naltrexone has been demonstrated (see, e.g. de Sousa and de Sousa, 2004, 2005; Laaksonen et al , 2008; Diehl et al ., 2010). However, safety issues with disulfiram (Chick, 1999) suggest the need for developing safer alternative ALDH inhibitors for alcoholism treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of acamprosate are only moderate in comparison with placebo and acamprosate has not been found to be consistently superior to naltrexone or disulfiram. Furthermore, there have not been any prospective studies evaluating the long-term (longer than one year) effectiveness of acamprosate in preventing lapse following discontinuation of the medication and retrospective studies have found the long-term effectiveness of acamprosate to be worse than that of disulfiram in a naturalistic clinical setting 61. Finally, it is imperative that more research be devoted to studying the mechanisms of efficacy for acamprosate and to determine whether certain patients are more or less likely to respond to this agent, as compared with other FDA-approved medications for alcohol dependence.…”
Section: Acamprosate In Clinical Practicementioning
confidence: 99%